1999
DOI: 10.1182/blood.v93.6.2013.406k25_2013_2024
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Lymphoid-Specific, Inducible Human Protein Tyrosine Phosphatase, Lyp

Abstract: Protein tyrosine phosphatases act in conjunction with protein kinases to regulate the tyrosine phosphorylation events that control cell activation and differentiation. We have isolated a previously undescribed human phosphatase, Lyp, that encodes an intracellular 105-kD protein containing a single tyrosine phosphatase catalytic domain. The noncatalytic domain contains four proline-rich potential SH3 domain binding sites and an NXXY motif that, if phosphorylated, may be recognized by phosphotyrosine binding (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
171
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(180 citation statements)
references
References 59 publications
2
171
0
4
Order By: Relevance
“…Lyp ⁄ Pep is a hematopoietic tyrosine phosphatase that contains an N-terminal phosphatase domain and four proline-rich domains, the most C-terminal of which lies within a 20 amino acid conserved region that defines a small family of phosphatases, the so-called PEST group (3,152,153) (Fig. 2).…”
Section: Lyp ⁄ Pep Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Lyp ⁄ Pep is a hematopoietic tyrosine phosphatase that contains an N-terminal phosphatase domain and four proline-rich domains, the most C-terminal of which lies within a 20 amino acid conserved region that defines a small family of phosphatases, the so-called PEST group (3,152,153) (Fig. 2).…”
Section: Lyp ⁄ Pep Structurementioning
confidence: 99%
“…The function of this conserved C-terminal domain remains unclear. Pep and Lyp are species orthologs but vary considerably in their C-terminal halves (153). There is 89% sequence homology between the phosphatase domains, but only 61% homology for the remaining portions of the proteins.…”
Section: Lyp ⁄ Pep Structurementioning
confidence: 99%
“…The PTPN22 gene is located at the chromosomal region 1p13.3-p13.1 and encodes the protein belonging the nonreceptor class 4 subfamily of the protein tyrosine phosphatase family. This protein is the intracellular lymphoid tyrosine phosphatase (LYP) (Cohen, Dadi, Shaoul, Sharfe, & Roifman, 1999) and it is only expressed in the immune cells, including dendritic and B cells, and particularly in T cells (Rhee & Veillette, 2012).…”
Section: Protein Tyrosine Phosphatase Nonreceptor 22: (Ptpn22)mentioning
confidence: 99%
“…PTP-HSCF appears to be primarily expressed in primitive hematopoietic cells, although it may also be present in other cell types (1)(2)(3)(4)(5)(6)(7)(8). All PEST family members reside in the cytoplasm, although some data suggested that a fraction of PEP may be found in the nucleus (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether a similar interaction also exists between LYP and Csk in normal human T cells. PEP ⁄ LYP also binds to Grb2 and c-Cbl (2,18). In contrast, PTP-PEST prominently associates with proteins involved in the organization of the cytoskeleton (13,16,(19)(20)(21)(22)(23)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%